PENGARUH PUPUK ORGANIK CAIR DAN PUPUK KOMPOS KULIT BUAH KAKAO TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis gueneensis Jacq.) DI PEMBIBITAN UTAMA. - Putra Panggabean; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to determine the best dose interaction and liquid organic fertilizer and compost rind cocoa to the growth of oil palm seedlings in Main nursery. The research was conducted from September 2014 to January 2015. The research was conducted using a completely randomized design consisting of two factors and three replications. The first factor is the provision of liquid organic reeds fertilizer with 4 dose level consisting (0, 50, 75 and 100 ml / 1 liter of water. The second factor is the provision of compost rind cocoa with 4 dose level consisting (0, 50, 100 and 150 g / 8 kg soil (37.5 tons / ha). Data were analyzed using analysis of variance followed by a further test DNMRT at 5% level. Parameters measured were high increment, in the number of leaves, tubers circumference, crown root ratio and seedling dry weight. The results showed that administration of a liquid organic fertilizer 50 ml / l and compost rind cocoa 150 g / polybag, showed increased growth of oil palm seedlings to the seedling height parameters, number of leaves, dry weight of seedlings and did not show an increase in the circumference hump and the ratio of the root crown   Keywords : oil palm, liquid organic fertilizer, compost rind cocoa